Effects of the Hydroethanolic Extract of Lycopodium selago L. on Scopolamine-Induced Memory Deficits in Zebrafish - Mihai-Vlad Valu; Catalin Ducu; Sorin Moga; Denis Negrea; Lucian Hritcu; Razvan Stefan Boiangiu; Emanuel Vamanu; Tudor Adrian Balseanu; Simone Carradori; Liliana Cristina Soare (MDPI AG, 2021)
This scientific research focused on the production of hydroethanolic extract of the plant species Lycopodium selago L. (L. selago) by the ultrasound-assisted extraction (USAE) and the identification of biocompounds with high antioxidant activity is of interest for possible phytotherapeutic treatment against Alzheimer's disease (AD). The extract was phytochemically analyzed to investigate polyphenols, flavonoids, and identify the sesquiterpenoid alkaloid huperzine A (HupA), which is known in the literature for its great relevance in AD. Evaluation and comparison of the antioxidant activity of the extract were performed by four complementary spectrophotometric methods (DPPH, FRAP, ABTS, ORAC). In vitro tests of the extract showed an excellent reciprocal link between the concentration of polyphenols and the measurement of the antioxidant activity of the extract with the sesquiterpenoid HupA. To confirm the antioxidant activity, L. selago hydroethanolic extract was administered in vivo to zebrafish (Danio rerio) with a pattern of scopolamine-induced cognitive impairment. Moreover, this study explored a possible correlation between the expression of oxidative stress markers in the brain tissue with the behavior of the scopolamine zebrafish model. In vivo tests showed that this fern could be used as a nutritional supply and as a phytotherapeutic method to prevent or treat various neurodegenerative diseases that call for high-nutritive-value medications.